(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
We consider a first-order nonlinear neutral differential equation. By employing Krasnoselskii’s fixed point theorem, we provide several new criteria for the existence of positive periodic solutions to this equation. The theorems we have formulated are exemplified through a specific example.